1992
DOI: 10.1093/carcin/13.12.2467
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of N-nitrosomethylbenzylamine bioactivation by diallyl sulfide in vivo

Abstract: Diallyl sulfide (DAS*), a major flavour and fragrance component of garlic oil (1), has been shown to be an effective inhibitor of tumorigenesis by diverse metabolically activated chemical carcinogens <2-5). In the most striking example of chemoprevention, Wargovich and co-workers reported (4) that pretreatment with DAS completely prevented the formation in rat oesophagus of both malignant and premalignant lesions by /V-nitrosomethylbenzylamine (NMBzA), an exceptionally potent and selective oesophageal carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Garlic sulfides have been reported to modulate P-450 isozymes (18)(19)(20)(21), block carcinogen activation (22)(23)(24)(25), diminish carcinogen-induced nuclear damage (22,26), and stimulate glutathione S-transferase (26)(27)(28)(29). Milner and coworkers (30,31) also showed that natural garlic and its constituents are able to inhibit the formation of DMBA-DNA adducts in rat mammary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic sulfides have been reported to modulate P-450 isozymes (18)(19)(20)(21), block carcinogen activation (22)(23)(24)(25), diminish carcinogen-induced nuclear damage (22,26), and stimulate glutathione S-transferase (26)(27)(28)(29). Milner and coworkers (30,31) also showed that natural garlic and its constituents are able to inhibit the formation of DMBA-DNA adducts in rat mammary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous garlic extracts reduced the mutagenicity of ionizing radiation, peroxides, Adriamycin, and N-methyl-N′-nitrosoguanidine (61). DAS diminished the DNA hypermethylation of esophagus, liver, and nasal mucosa that arose from treatment with N-nitrosomethylbenzylamine (62). However, Cohen et.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…DNA methylation and histone acetylation can be modified by enhanced intake of garlic and/or related allyl sulfur compounds. In another study Leudeke et al [103] reported that DAS inhibited the formation of O 6 -methyldeoxy guanosine in esophagus (26%), nasal mucosa (51%), trachea (68%) and lung (78%) induced by N-nitrosomethyl benzylamine. Similarly, Lin et al [94] and Schaffer et al [104] provide evidences that DAD, SAC and deodorized garlic are effective in retarding the DNA methylation caused by N-methyl-N-nitrosourea.…”
Section: Mechanism Of Actionmentioning
confidence: 96%